The Arab center : the promise of moderation - Muasher, Marwan (Yale University Press, 2008)
Muasher, a prominent Jordanian diplomat, recounts the behind-the-scenes details of diplomatic ventures over the past two decades, including such recent undertakings as the Arab Peace Initiative and the Middle East Road Map.